Peningkatan Kompetensi Guru BK dalam Layanan Bimbingan Klasikal melalui Lesson Study Berbasis Sekolah (LSBS) (Jurnal Bimbingan dan Konseling Islam, 2018)
The purpose of this research is to improve the competence of teacher guidance and counseling in classical guidance services through a school-based lesson study (LSBS) in District Jatinangor Sumedang. The used approach is a quantitative study with single-subject design with a pattern AB. Research carried out by conducting a preliminary study, the measurement of the baseline condition three times, the provision of school-based interventions lesson study conducted four sessions once a week while the measurament intervention condition, and data analysis. The results of a preliminary study of 101 guidance and counseling teachers competence showed that 77 teachers were included in competent category, 24 teachers were incompetent teachers. Than it was measured by baseline, there 3 guidance and counseling teachers were incompetent. Empirical test results showed that school-based lesson study can improve the competence of guidance and counseling teachers in junior high school Jatinangor Sumedang District. The implementation of classical guidance services through school-based lesson study can improve the competence of the 3 guidance and counseling teachers in many aspects: 1) Mastering the theoretical framework and practical guidance and counseling, (2) Mastering the concepts and practice of assessment to understand the conditions, the needs and the problems of the counselee, (3) Designing the guidance and counseling program, (4) Assessing the process and results of operations guidance and counseling.